2022
DOI: 10.1080/07853890.2022.2057581
|View full text |Cite
|
Sign up to set email alerts
|

Current methods for developing predictive energy equations in maintenance dialysis are imprecise

Abstract: Purpose For individuals receiving maintenance dialysis, estimating accurate resting energy expenditure (REE) is essential for achieving energy balance, and preventing protein-energy wasting. Dialysis-specific, predictive energy equations (PEEs) offer a practical way to calculate REE. Three PEEs have been formulated via similar methods in different demographic samples; the Maintenance Haemodialysis Equation (MHDE REE), Vilar et al. Equation (Vilar REE) and the Fernandes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…To date, dialysis-specific EEs have improved predictive accuracy by achieving around 60% precision (± 10% of zero difference from mREE) when tested in samples of people with similar characteristics to the development group [ 20–25 ]. However, our group has demonstrated that disease-specific EEs may not perform well when transferred to different geographical or demographic samples, or to those people with outlying characteristics, such as very low or high body mass index (BMI) [ 27 ]. Arguably, such individuals may be the most vulnerable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, dialysis-specific EEs have improved predictive accuracy by achieving around 60% precision (± 10% of zero difference from mREE) when tested in samples of people with similar characteristics to the development group [ 20–25 ]. However, our group has demonstrated that disease-specific EEs may not perform well when transferred to different geographical or demographic samples, or to those people with outlying characteristics, such as very low or high body mass index (BMI) [ 27 ]. Arguably, such individuals may be the most vulnerable.…”
Section: Introductionmentioning
confidence: 99%
“…The Rutgers Nutrition and Kidney Database (RNKD) is a large renal database in the USA, containing over 600 clinical and demographic variables gathered for 210 hemodialysis patients over 4 separate studies undertaken between 2012 and 2018 [ 27 ]. Using this database, the primary objective of this pilot study was to ascertain if a machine learning approach alone can generate a more precise estimation of REE than previous statistical methods using linear and logistical regression only [ 20–25 ].…”
Section: Introductionmentioning
confidence: 99%
“…CKD progresses to a terminal stage termed as end-stage renal disease (ESRD), requiring renal replacement therapy (hemodialysis, peritoneal dialysis, and kidney transplantation). According to the Renal Data System, the number of patients with ESRD requiring renal replacement therapy is increasing year by year in the United States, reaching nearly 7,50,000 in 2019 ( 1 ). Sixty-three percent of these individuals receive maintenance hemodialysis (MHD) ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Renal Data System, the number of patients with ESRD requiring renal replacement therapy is increasing year by year in the United States, reaching nearly 7,50,000 in 2019 ( 1 ). Sixty-three percent of these individuals receive maintenance hemodialysis (MHD) ( 1 ). Despite improving survival rates, only 57% of MHD patients are still alive 3 years after their first treatment ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation